PERSEPSI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN HUTAN KEMASYARAKATAN DI DESA PISANG KECAMATAN JANGKANG KABUPATEN SANGGAU - Prawitmo, Albertus; Purwati, .; AM, Iskandar (JURNAL HUTAN LESTARI, 2017)
The Community Forest are governmental programs in an effert to empower the community to utilize state forests. This research aims to describe the public perception of the development planning of the community fores in Rosak Hamled and Entawak Hamlet of Pisang village of the subdistrict of Jangkang in Sanggau Regency and to analyze the correlation between the following factor: age, knowledge, cosmopolitanism, income forest. The method used in this research is survey method with interview techniques and the tool used for the data collection was the questionnaire. The perceptions tends to be positive regarding the development planning of the community forest in Pisang village of Jangkang subdistrict in Sanggau by 49.28%. it shows that the community agrees with the program of the government to develop the community forest in Pisang village area. The analysis of Chi Square shows that there was significant correlation between the age, knowledge, cosmopolitanism, income, and benefits of the outreach on the public perception regarding the development planning of the community forest in Pisang village. To the Local Government (Regency) may help and facilitate the community in an optimally function from the HKm development and management plan as well included intensive extension efforts to farmer groups both formally and informally. Keywords: Community forest, Development, Perception, Planning